GENERALIZED ESTIMATING EQUATION IN PHARMACOLOGICAL STUDY - Tripathi, *A.; Bora, M.; Dr, Lalrinpuia; Mukherjeeherjee, K.; Upadhaya, S. N. (International Journal of Ayurveda and Pharma Research, 2018)
Generalized Estimating Equation (GEE) deals with such data that do not have normal distribution in case of repeated experiment and has better properties as compared to rANOVA. With the objective to describe the use of GEE in pharmacological study this endeavour started. GEE described hereby using rat data. Four correlation structured were taken in GEE. It was found Independent/Exchangeable structure best suited with data. The model fit on data was assessed graphically as well. The trend line of repeated data for all cases (rats) were fallen in 95 % bound of predicted model. The model gave the average weight of rat 226.51 gram with start of experiment and it increases 8.67gram per week after feeding high fat diet.